Current Uses and Pitfalls of Liquid Biopsy in NSCLC (Canadian Oncology Today, 2024)
Liquid biopsy has emerged as an important tool in the diagnosis and management of lung and other cancers. Various analytes and analytical methods have been studied, including genomic testing by next-generation sequencing (NGS) and non-NGS approaches, including those examining methylation or DNA fragment size. Liquid biopsy, especially from plasma or blood, has several advantages over percutaneous or endoscopic tissue biopsy. It is less invasive, can be used serially for monitoring, and better reflects tumoural heterogeneity across metastatic sites, as opposed to a single area of the biopsied tumour. Herein, we highlight the current uses of liquid biopsy using circulating tumour DNA (ctDNA) analysis in routine clinical practice and potential pitfalls.